2018
DOI: 10.1016/j.applthermaleng.2017.08.173
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of a new concept of solar external receiver: Variable velocity receiver

Abstract: The deployment of new solar power tower plants mainly depends on becoming costcompetitive with traditional forms of electricity generation. The solar field represents around 40% of the solar power tower investment cost, thus the cost reduction of such subsystems is mandatory to achieve that goal. This reduction could be done by increasing the solar flux intercepted by the receiver, which would increase the peak flux. Therefore, new concepts of solar receivers are required to accommodate such high peak flux.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The lowest maximum wall temperature in the whole receiver corresponds to k=1.5 instead of k=1. Although, the spillage losses are lower in k=1.5 than in k=1 (higher average heat flux), the flux distribution in k=1.5 is more homogeneous than in k=1, see (Rodríguez-Sánchez et al, 2018), and then the peak flux and then the maximum wall temperature in the whole receiver are lower. For the receiver analysed and a given aiming factor, the CGM underestimates the maximum wall temperature and the thermal stresses of the whole reciever around 10 °C and 3MPa, respectively.…”
Section: Model Comparison For the Case Of A Real Aiming Strategymentioning
confidence: 96%
“…The lowest maximum wall temperature in the whole receiver corresponds to k=1.5 instead of k=1. Although, the spillage losses are lower in k=1.5 than in k=1 (higher average heat flux), the flux distribution in k=1.5 is more homogeneous than in k=1, see (Rodríguez-Sánchez et al, 2018), and then the peak flux and then the maximum wall temperature in the whole receiver are lower. For the receiver analysed and a given aiming factor, the CGM underestimates the maximum wall temperature and the thermal stresses of the whole reciever around 10 °C and 3MPa, respectively.…”
Section: Model Comparison For the Case Of A Real Aiming Strategymentioning
confidence: 96%
“…The bayonet design exhibits promising results when compared to conventional molten salt receiver tubes [68], with thermal efficiency improvements of 2% and maximum wall temperature reductions of > 100 • C reported. A variable velocity (VVR) molten salt cylindrical receiver concept is proposed by Rodríguez-Sánchez et al [72], with the thermal model presented by Ref. [68] used to investigate thermohydraulic performance.…”
Section: Novel Receiver Conceptsmentioning
confidence: 99%
“…Alternate methods of aiming (Garcí a et al, 2020;Acosta et al, 2021) 3. Modifying the heat transfer properties of the system by changing the operating conditions (Zhang et al, 2013;Rodríguez-Sánchez et al, 2018) Single point aiming strategy, which was first suggested by reference (Vant-Hull, 2002), is investigated by various researchers (Sanchez-Gonzalez et al, 2017;Garcí a et al, 2020). However, the flux profile produced by this singleparameter aiming strategy is rather irregular, with different amplitudes along the receiver height.…”
Section: Introductionmentioning
confidence: 99%